A Study on Internet of Things(IoT) - Sanguida, NS; Sasikala, M (International Journal of Computer Sciences and Engineering, 2025)
Internet of Things is a new pattern which provides a set of new services for the next form of technological development. IOT in the sense, it is a “universal global neural network” in the cloud which connects various things. The form of communication that is either human-device, or human-human but the Internet of Things (IoT) promises a great future for the internet where the type of communication is machine-machine (M2M). This paper aims to provide a future vision , IoT Architecture , Applications and its Challenges